"I'd like to be under the sea": Contextual cues in virtual environments influence the orientation of idea generation. (January 2019) - Nelson, Julien; Guegan, Jérôme
Abstract: Several studies have urged to explore the connections between virtual environments and creativity, both to study the processes underlying creativity and to support improved performance in creative tasks. Virtual environments, in particular, allow fine control over contextual cues present in the environment, which may serve as inspiration for creative work. However, using this potential to the fullest requires a detailed understanding of how the environment may influence creative processes. The literature suggests that contextual cues present in the environment may guide the exploration of specific categories of ideas, leading to increased originality; but also that examples of solutions – which are, undoubtedly, contextual cues themselves – may lead to reduced creativity through a conformity effect. We successively conducted two experiments in virtual environments. In the first, we manipulated the contents of the environment to prime specific concepts – water or forest – and examined the effects on creative output in a divergent thinking task. In the second experiment, we manipulated the nature of the environment and the presence or absence of examples of solutions, and examined the output of a task involving drawing alien creatures. In both experiments, the contents of environment influenced the nature of the creative output by priming specific concepts. Highlights: We examine effects of exposure to virtual environments on output in creative tasks. Two studies examine this influence in terms of priming and conformity effects. Contextual cues present in the virtual environment may prime specific concepts. Raises questions about the design of virtual environments to support creative work.